1979
DOI: 10.1073/pnas.76.9.4331
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adult, embryonic, and dystrophic myosin heavy chains from chicken muscle by sodium dodecyl sulfate/polyacrylamide gel electrophoresis and peptide mapping.

Abstract: Chicken myosin heavy chains from adult fast white muscle fibers (both normal and dystrophic), adult slow red fibers, and embryonic presumptive fast white fibers were compared by sodium dodecyl sulfate/polyacrylamide gel electrophoresis and by peptide mapping. The heavy chain of slow red myosin migrated electrophoretically more slowly than the heavy chains of the other myosins and differed markedly from them in its peptide maps. The heavy chain of dystrophic fast white myosin was similar to its normal counterpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
1

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 26 publications
(22 reference statements)
1
49
1
Order By: Relevance
“…These results could also be consistent with the expression of a distinct embryonic isomyosin (1)(2)(3)(4)(5)(6)(7)(8), because our anti-skeletal antibodies cross-react with embryonic as well as adult skeletal myosins. However, our results indicate that these patterns of myosin expression do not apply to the initial developmental program for the myotome.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These results could also be consistent with the expression of a distinct embryonic isomyosin (1)(2)(3)(4)(5)(6)(7)(8), because our anti-skeletal antibodies cross-react with embryonic as well as adult skeletal myosins. However, our results indicate that these patterns of myosin expression do not apply to the initial developmental program for the myotome.…”
Section: Discussionsupporting
confidence: 77%
“…However, there has been considerable controversy as to the nature of both the heavy-chain and light-chain subunit composition of the myosin isozymes expressed in embryonic muscle. With respect to heavy-chain composition, there are several lines of evidence to suggest that skeletal muscle development is characterized by the expression of a distinct embryonic isomyosin (1)(2)(3)(4)(5)(6)(7)(8). Other evidence has suggested that the developmental program for embryonic skeletal muscle involves either the expression of fast skeletal myosin initially (10), the coexpression offast and slow skeletal isomyosins (7,9), or the expression of cardiac as well as skeletal isomyosins (11,17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This enzymatic activity is correlated with contractile velocity in skeletal muscle (1) and thus appears to be an important determinant of contractile function. Numerous polymorphic forms of myosin HC exist, not only in different types of muscle-e.g., fast and slow skeletal and cardiac-but also within each muscle type (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Expression of these forms follows a developmental pattern (12)(13)(14)(15)(16)(17)(18) that may be altered by changes in the physiological (19)(20)(21) and hormonal (10)(11)(12)(13) milieu ofthe cell.…”
mentioning
confidence: 99%
“…The specific activity ofthe probe was 1-5 X 10r' cpm/yg. Hybridization and nuclease S1 digestion were carried.out by the method of Orkin and Goff (38), except that the probe (0.5-1 X 105 cpm, 10-50 ng) was hybridized in a sealed capillary tube with either 5 ,ug of cardiac poly(A)+RNA or 30-50 pg of cardiac total RNA. The digested products were analyzed on 5% sequencing gels (33,38).…”
mentioning
confidence: 99%